PENARAPAN METODE GOAL PROGRAMMING UNTUK MENGOPTIMALKAN BEBERAPA TUJUAN PADA PERUSAHAAN DENGAN KENDALA JAM KERJA, PERMINTAAN DAN BAHAN BAKU - Fauziyah Fauziyah (Jurnal Matematika MANTIK, 2016)
The company has multiple objectives that want to be achieved, which are maximizing selling, maximizing production and minimizing the cost production without reducing the quality of the product. The objective contains different aspects and so often incompatible with each other. To provide an optimal solution with respect to those objectives of some predetermined goals, the applied method that used is goal programming. The goal programming show that it is run by using the LINDO program. The result of the goal programming method can maximize the total selling and total production by minimize cost. The result showed that the define objectives achieved optimally